Sodium-ion battery cathode materials and their preparation methods, sodium-ion batteries
By combining the O3-type positive electrode material matrix doped with Ta and Ce doped with Ti-doped P2-type positive electrode material layer in the sodium-ion battery positive electrode material, the diffusion kinetics of the sodium-ion battery positive electrode material is solved by combining the Ta and Ce doped with Ti-doped P2-type positive electrode material layer in the sodium-ion battery positive electrode material layer, and adding an ion conductor material layer, the diffusion kinetics of the sodium-ion battery positive electrode material is solved. and stability issues have achieved efficient electrochemical performance and cyclic stability improvement.
Patent Information
- Application Number
- CN202411067002.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-08-06
AI Technical Summary
The existing positive electrode materials of sodium ion batteries have problems such as slow Na+ diffusion kinetics, large interfacial charge transfer impedance and poor stability, which limits the application of sodium ion batteries in the energy storage field.
Using a combined structure of the O3 type positive electrode material matrix, the P2 type sodium ion positive electrode material layer and the ion conductor material layer, the sodium metal oxide doped by Ta and Ce is used as the O3 type positive electrode material matrix, and the Ti-doped sodium metal oxide is used as the The P2 type positive electrode material layer is calcined at high temperature to form a multi-layer structure of sodium ion battery positive electrode material.
The excellent structural stability, interface stability, low interface impedance, good air stability and high safety of the positive electrode material of sodium ion battery are achieved, which improves electrochemical performance and cyclic stability, while improving specific capacity and structural stability. .
Smart Images

Figure CN118588916B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion battery materials, and in particular relates to a sodium ion battery positive electrode material and a preparation method thereof. Background Art
[0002] Sodium-rich layered oxides are considered to be ideal commercial materials due to their low cost, simple preparation method, and energy density similar to that of lithium iron phosphate. However, there are still many problems, including Na + Slow diffusion kinetics, large interface charge transfer impedance, poor stability, etc. These problems limit the application of sodium ion batteries in the field of energy storage. Currently, doping modification and interface regulation have been considered to be effective means to improve the overall performance of batteries.
[0003] Although doping can effectively smooth the electrochemical curve, reduce the order of sodium vacancies, and inhibit harmful phase changes, there are interactions and repulsions between the doped metal elements, which are prone to produce lattice defects, which significantly reduce the initial specific capacity of the material, and cannot prevent H2O and CO2 in the air from contacting the active material to generate surface residual alkali. Although interface regulation effectively improves the interface stability of the material, the traditional inert coating will further reduce the ion diffusion kinetics and increase the interface charge transfer impedance.
[0004] Therefore, there is an urgent need to find a new material that can fully utilize the theoretical specific energy of the material under a wide voltage window, inhibit intergranular cracks, grain crushing, transition metal dissolution and other problems; and have both excellent actual capacity and stability. Summary of the invention
[0005] In response to the above technical problems, the present application provides a sodium ion battery positive electrode material and a preparation method thereof, and a sodium ion battery.
[0006] To achieve the above objectives, this application proposes the following technical solutions:
[0007] In a first aspect, a sodium ion battery positive electrode material is provided, comprising an O3 type positive electrode material matrix and a P2 type sodium ion positive electrode material layer and an ion conductor material layer sequentially arranged from the inside to the outside on the surface of the matrix; the O3 type positive electrode material matrix is a sodium metal oxide doped with Ta and Ce; and the P2 type sodium ion positive electrode material is a sodium metal oxide doped with Ti.
[0008] Furthermore, the chemical formula of the Ta and Ce doped sodium metal oxide is Na(Ni 0.3 Fe 0.3 Mn 0.4 ) y1 (Ta 0.5 Ce 0.5 ) z1 O2, of which 0.8 <y1≤0.9,0.1<z1≤0.2。
[0009] Furthermore, the chemical formula of the Ti-doped sodium metal oxide is Na t (Ni 0.2 Fe 0.3 Mn 0.5 ) y2 Ti z2 O2, of which 0.44 <t≤0.8,0.8<y2≤0.9,0.1<z2≤0.2。
[0010] Furthermore, the ion conductor material is Na3Zr2Si2PO 12 .
[0011] Furthermore, the mass ratio of the matrix to the P2 type sodium ion positive electrode material is 1:5~25wt%.
[0012] Furthermore, the mass ratio of the matrix to the ion conductor material is 1:5~10wt%.
[0013] In a second aspect, a method for preparing a positive electrode material for a sodium ion battery is provided, comprising:
[0014] S1. preparing an O3 type positive electrode material matrix, wherein the O3 type positive electrode material matrix is a sodium metal oxide doped with Ta and Ce;
[0015] S2, preparing a P2 type sodium ion cathode material precursor by an oxalic acid precursor method;
[0016] S3, mixing the O3 type positive electrode material matrix with the P2 type sodium ion positive electrode material precursor, and calcining to obtain a material A in which the P2 type sodium ion positive electrode material is coated with the O3 type positive electrode material matrix;
[0017] S4. Material A is mixed with an ion conductor material, and then calcined to obtain a sodium ion battery positive electrode material in which the ion conductor material coats the material A.
[0018] Furthermore, in step S3, the calcination temperature is 700-900° C. and the calcination time is 12-24 hours.
[0019] Furthermore, in step S4, the calcination temperature is 400-600° C. and the calcination time is 12-18 hours.
[0020] Further, step S1 comprises: using sodium source, nickel source, iron source, manganese source, tantalum source and cerium source as raw materials, wet mixing and ball milling, spray drying to obtain a mixed powder, and high temperature sintering the mixed powder to obtain an O3 type positive electrode material matrix Na (Ni 0.3 Fe 0.3 Mn 0.4 ) y1 (Ta0.5 Ce 0.5 ) z1 O2, of which 0.8 <y1≤0.9,0.1<z1≤0.2。
[0021] Furthermore, in step S1, the sodium source is one or more of sodium oxide, carbonate, hydroxide, and oxalate; the nickel source is one or more of nickel oxide, hydroxide, carbonate, oxalate, acetate, and nitrate; the iron source is one or more of iron oxide, hydroxide, carbonate, oxalate, acetate, and nitrate; the manganese source is one or more of manganese oxide, hydroxide, carbonate, oxalate, acetate, and nitrate; the tantalum source is one or more of tantalum oxide, hydroxide, carbonate, oxalate, acetate, and nitrate; the cerium source is one or more of cerium oxide, hydroxide, carbonate, oxalate, acetate, and nitrate.
[0022] Furthermore, in step S1, the temperature of the high temperature sintering is 700-900° C., and the time of the high temperature sintering is 12-18 hours.
[0023] Furthermore, step S2 comprises: adding a sodium source, an iron source, a nickel source, a manganese source and a titanium source into an oxalic acid solution, reacting, and drying to obtain an oxalate precursor.
[0024] Furthermore, in step S2, the sodium source is one or more of sodium oxide, carbonate, and oxalate; the nickel source is one or more of nickel oxide, hydroxide, carbonate, oxalate, and acetate; the manganese source is one or more of manganese oxide, hydroxide, carbonate, oxalate, and acetate; the iron source is one or more of iron oxide, hydroxide, carbonate, oxalate, and acetate; and the titanium source is titanium oxalate.
[0025] In a third aspect, a sodium ion battery is provided, comprising the aforementioned sodium ion battery positive electrode material or the sodium ion battery positive electrode material prepared by the aforementioned preparation method.
[0026] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects:
[0027] (1) The positive electrode material of a sodium ion battery comprises a doped sodium-rich core material, a doped sodium-deficient sub-layer material and an outermost layer material with high ionic conductivity. The positive electrode material of a sodium ion battery has the advantages of excellent structural stability, interface stability, low interface impedance, good air stability and high safety. When used in sodium ion batteries, it has excellent electrochemical performance and cycle stability.
[0028] (2) The sodium-rich structure of the positive electrode material of the sodium-ion battery provides a higher specific capacity. The doping of Ta and Ce ions into the sodium-rich main structure can expand the ion channel, increase the ion transmission speed, and improve the electrochemical performance of the positive electrode material of the sodium-ion battery. The sodium-deficient sub-outer layer can effectively reduce the Na + The diffusion energy barrier of Ti ions can enhance the structural stability and improve the electrochemical performance of the sodium-deficient sub-outer layer. The outermost structure can stabilize the electrochemical interface and enhance the ion diffusion kinetics, further ensuring that the sodium-ion battery has better structural stability and electrochemical performance.
[0029] (3) During the preparation of the positive electrode material for sodium batteries, the doped sub-outer layer material is evenly distributed on the surface of the core material. After the outermost layer material is introduced, the core, outermost layer, and sub-outer layer materials are tightly connected by utilizing the diffusion of ions at high temperature, which is beneficial to further improve the discharge specific capacity and structural stability of the positive electrode material.
[0030] (4) The process flow for preparing positive electrode materials for sodium ion batteries is simple and controllable, low-cost and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is the XRD diffraction pattern of the core material prepared in step (2) of Example 1.
[0033] Figure 2 This is the XRD diffraction pattern of the material obtained after sintering the sub-outer layer material prepared in step (3) of Example 1.
[0034] Figure 3 This is the SEM image of the positive electrode material prepared in Example 1.
[0035] Figure 4 This is the XRD diffraction pattern of the positive electrode material prepared in Example 1.
[0036] Figure 5 The cycle performance diagram of button-type batteries assembled with positive electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 5. DETAILED DESCRIPTION
[0037] The present invention provides a sodium ion battery positive electrode material, comprising an O3 type positive electrode material matrix and a P2 type sodium ion positive electrode material layer and an ion conductor material layer sequentially arranged from the inside to the outside on the surface of the matrix; the O3 type positive electrode material matrix is a sodium metal oxide doped with Ta and Ce; and the P2 type sodium ion positive electrode material is a sodium metal oxide doped with Ti.
[0038] In some preferred embodiments, the chemical formula of the Ta and Ce doped sodium metal oxide is: Na(Ni 0.3 Fe 0.3 Mn 0.4 ) y1 (Ta 0.5 Ce 0.5 ) z1 O2, of which 0.8 <y1≤0.9,0.1<z1≤0.2。
[0039] In some preferred embodiments, the chemical formula of the Ti-doped sodium metal oxide is: Na t (Ni 0.2 Fe 0.3 Mn 0.5 ) y2 Ti z2 O2, of which 0.44 <t≤0.8,0.8<y2≤0.9,0.1<z2≤0.2。
[0040] In some preferred embodiments, the ion conductor material layer is Na3Zr2Si2PO 12 .
[0041] In some preferred embodiments, the mass ratio of the matrix to the P2-type sodium ion positive electrode material is 1:5~25wt%.
[0042] In some preferred embodiments, the mass ratio of the matrix to the ion conductor material is 1:5-10wt%.
[0043] The present invention also provides a method for preparing a positive electrode material for a sodium ion battery, comprising:
[0044] S1. preparing an O3 type positive electrode material matrix, wherein the O3 type positive electrode material matrix is a sodium metal oxide doped with Ta and Ce;
[0045] S2, preparing a P2 type sodium ion cathode material precursor by an oxalic acid precursor method;
[0046] S3, mixing the O3 type positive electrode material matrix with the P2 type sodium ion positive electrode material precursor, and calcining to obtain a material A in which the P2 type sodium ion positive electrode material is coated with the O3 type positive electrode material matrix;
[0047] S4. After mixing Material A with an ionic conductor material and then performing calcination, a sodium-ion battery positive electrode material in which the ionic conductor material coats Material A is obtained.
[0048] In some preferred embodiments, in step S3, the calcination temperature is 700 - 900 °C; the calcination time is 12 - 24 h.
[0049] In some preferred embodiments, in step S4, the calcination temperature is 400 - 600 °C; the calcination time is 12 - 18 h.
[0050] The O3-type sodium-rich positive electrode material matrix can be prepared by using raw materials for solid-phase sintering method, or by spray drying to prepare a precursor, and then mixing and sintering the precursor with a sodium source. It can also be prepared by first performing wet ball milling to prepare a raw material mixed slurry, then performing spray drying to prepare a precursor, and finally mixing and sintering the precursor with a sodium source.
[0051] In some embodiments, step S1 includes: using a sodium source, a nickel source, an iron source, a manganese source, a tantalum source, and a cerium source as raw materials, performing wet mixing and ball milling, then performing spray drying to obtain a mixed powder, and performing high-temperature sintering on the mixed powder to obtain an O3-type positive electrode material matrix Na(Ni 0.3 Fe 0.3 Mn 0.4 ) y1 (Ta 0.5 Ce 0.5 ) z1 O2, where 0.8 < y1 ≤ 0.9 and 0.1 < z1 ≤ 0.2. The raw materials required by this method can be soluble raw materials or insoluble raw materials.
[0052] In some embodiments, in step S1, the sodium source is one or more of sodium oxides, carbonates, hydroxides, oxalates; the nickel source is one or more of nickel oxides, hydroxides, carbonates, oxalates, acetates, nitrates; the iron source is one or more of iron oxides, hydroxides, carbonates, oxalates, acetates, nitrates; the manganese source is one or more of manganese oxides, hydroxides, carbonates, oxalates, acetates, nitrates; the tantalum source is one or more of tantalum oxides, hydroxides, carbonates, oxalates, acetates, nitrates; the cerium source is one or more of cerium oxides, hydroxides, carbonates, oxalates, acetates, nitrates.
[0053] In step S1, the solid-liquid ratio of wet mixing and ball milling can be in accordance with a conventional ratio and ensure that spray drying can be achieved subsequently. Specifically, it can be 20 - 60:100 g / mL.
[0054] In some implementation modes, in step S1, the temperature of the high temperature sintering is 700-900° C., and the time of the high temperature sintering is 12-18 hours.
[0055] In some preferred embodiments, step S2 comprises: adding a sodium source, an iron source, a nickel source, a manganese source and a titanium source into an oxalic acid solution, reacting the solution and drying the solution to obtain an oxalate precursor.
[0056] During the preparation of the oxalic acid precursor, the material is slowly added into the oxalic acid solution.
[0057] In some preferred embodiments, the amount of oxalic acid used can be 1 to 2 times the theoretical amount required for the reaction.
[0058] In some preferred embodiments, the concentration of the oxalic acid solution is 4 mol / L.
[0059] In some preferred embodiments, in step S2, the sodium source is one or more of sodium oxide, carbonate, and oxalate; the nickel source is one or more of nickel oxide, hydroxide, carbonate, oxalate, and acetate; the manganese source is one or more of manganese oxide, hydroxide, carbonate, oxalate, and acetate; the iron source is one or more of iron oxide, hydroxide, carbonate, oxalate, and acetate; and the titanium source is titanium oxalate.
[0060] The present invention also provides a sodium ion battery, comprising the aforementioned sodium ion battery positive electrode material or the sodium ion battery positive electrode material prepared by the aforementioned preparation method.
[0061] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.
[0062] Example 1
[0063] A method for preparing a positive electrode material for a sodium ion battery, comprising:
[0064] (1) Weigh a certain amount of sodium carbonate, NiO, MnO2, Fe2O3, Ta2O5, and CeO2 as raw materials, where the molar ratio of sodium, nickel, manganese, iron, tantalum, and cerium is 10.3:2.4:2.4:3.2:1:1, and pour them into a ball mill. Add a certain amount of pure water to the ball mill to make the solid-liquid ratio 20:100 g / mL, mix in the ball mill for 1 hour at a speed of 600 rpm, and then transfer the powder to a spray dryer. Adjust the feed rate to 15 ml / min, the inlet air temperature to 180-220 °C, the atomization pressure to 0.2 MPa, and the outlet air temperature to 100 °C. Transfer the prepared product to a muffle furnace and sinter it at 900 °C for 12 hours. After natural cooling, the core material is obtained. The XRD pattern is as follows: Figure 1As shown, from Figure 1 It can be seen that the material is a pure O3 phase material. According to the raw materials, the chemical formula of the core material is estimated to be Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.8 (Ta 0.5 Ce 0.5 ) 0.2 O2.
[0065] (2) Preparation of the sub-outer layer material: weigh Na2CO3, Ni(OH)2, Fe2O3, MnO2, and Ti(C2O4)2 according to the stoichiometric ratio of 7:1.6:2.4:4:2 for the atoms of sodium, nickel, iron, manganese, and titanium, and slowly add them to 50 ml (4 mol / L) of oxalic acid solution while stirring. After the reaction is complete, transfer to a drying oven at 70°C and dry for 12 hours to obtain the sub-outer layer material precursor 2. Take part of the sub-outer layer material precursor 2 and sinter it in a muffle furnace at 900°C for 12 hours. The XRD pattern of the obtained material is shown in the figure below. Figure 2 As shown, from Figure 2 It can be seen that the material is a pure phase P2 phase material. According to the raw materials, it is speculated that the secondary outer layer material precursor 2 is a P2 phase positive electrode material Na 0.7 (Ni 0.2 Fe 0.3 Mn 0.5 ) 0.8 Ti 0.2 Precursor of O2.
[0066] (3) Take 10g of the core material and 1g of the precursor 2, mix them in a ball mill for 1 hour (speed is 300rpm), and then sinter them in a muffle furnace at 900℃ for 12h to obtain material 1. Then, the outer layer material is evenly distributed on the surface of the core material, and the chemical formula is: Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.8 (Ta 0.5 Ce 0.5 ) 0.2 O2@Na 0.7 (Ni 0.2 Fe 0.3 Mn 0.5 ) 0.8 Ti 0.2 O2.
[0067] (4) Take 10g of material 1 and 0.8g of Na3Zr2Si2PO 12 The material was mixed in a ball mill for 1 hour at a speed of 300 rpm, then calcined in a muffle furnace at 500°C for 15 hours, and naturally cooled to room temperature to obtain a positive electrode material. The SEM image of the obtained positive electrode material is shown in Figure 3 As shown; the XRD pattern of the obtained positive electrode material is shown Figure 4 As shown, from Figure 4 It can be seen that the positive electrode material includes characteristic peaks corresponding to the O3 phase and P2, and no other obvious impurity peaks can be seen. The chemical formula of the final positive electrode material is Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.8 (Ta 0.5 Ce 0.5 ) 0.2 O2@Na 0.7 (Ni 0.2 Fe 0.3 Mn 0.5 ) 0.8 Ti 0.2 O2@Na3Zr2Si2PO 12 .
[0068] Comparative Example 1
[0069] A method for preparing a positive electrode material for a sodium ion battery, comprising:
[0070] Weigh a certain amount of sodium carbonate, NiO, MnO2, Fe2O3, Ta2O5, and CeO2 as raw materials, where the molar ratio of sodium, nickel, manganese, iron, tantalum, and cerium is 10.3:2.4:2.4:3.2:1:1, pour into a ball mill, add a certain amount of pure water to the ball mill to make the solid-liquid ratio 20:100 g / mL, mix in the ball mill for 1 hour at a speed of 600rpm, and then transfer the powder to a spray dryer, adjust the feed rate to 15ml / min, the inlet air temperature to 180~220℃, the atomization pressure to 0.2Mpa, and the outlet air temperature to 100℃. The prepared product is then transferred to a muffle furnace for sintering at 900℃ for 12h, and naturally cooled to room temperature to obtain a positive electrode material with a chemical formula of Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.8 (Ta 0.5 Ce 0.5 ) 0.2 O2.
[0071] Comparative Example 2
[0072] A method for preparing a positive electrode material for a sodium ion battery, comprising:
[0073] (1) Preparation of Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.8 (Ta 0.5 Ce 0.5 )0.2 The O2 material process is consistent with Example 1.
[0074] (2) Weigh Na2CO3, MnO2, Ni(OH)2, Fe2O3, and Ti(C2O4)2 according to the stoichiometric ratio of 7:1.6:2.4:4:2 for the atoms of sodium, nickel, iron, manganese, and titanium, and slowly add them to 50 ml (4 mol / L) of oxalic acid solution while stirring. After the reaction is complete, transfer to a drying oven at 70°C and dry for 12 hours to obtain precursor 2.
[0075] (3) Take 10g Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.8 (Ta 0.5 Ce 0.5 ) 0.2 O2 material, 1g of precursor 2, was mixed in a ball mill for 1 hour (rotation speed was 300rpm), then calcined in a muffle furnace at 900℃ for 12h, and naturally cooled to room temperature to obtain the positive electrode material with the chemical formula of Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.8 (Ta 0.5 Ce 0.5 ) 0.2 O2@Na 0.7 (Ni 0.2 Fe 0.3 Mn 0.5 ) 0.8 Ti 0.2 O2.
[0076] Comparative Example 3
[0077] A method for preparing a positive electrode material for a sodium ion battery, comprising:
[0078] (1) Preparation of Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.8 (Ta 0.5 Ce 0.5 ) 0.2 The O2 material process is consistent with Example 1.
[0079] (2) Take 10g Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.8 (Ta 0.5 Ce 0.5 ) 0.2 O2 and 0.8g Na3Zr2Si2PO 12The material was mixed in a ball mill for 1 hour (rotation speed was 300 rpm), then calcined in a muffle furnace at 500 ° C for 15 hours, and naturally cooled to room temperature to obtain a positive electrode material with a chemical formula of Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.8 (Ta 0.5 Ce 0.5 ) 0.2 O2@Na3Zr2Si2PO 12 .
[0080] Comparative Example 4
[0081] A method for preparing a positive electrode material for a sodium ion battery, comprising:
[0082] (1) Weigh a certain amount of sodium carbonate, NiO, MnO2, and Fe2O3 as raw materials, where the molar ratio of sodium, nickel, manganese, and iron is 10.3:3:3:4, and pour them into a ball mill. Add a certain amount of pure water to the ball mill to make the solid-liquid ratio 20:100 g / mL, mix in the ball mill for 1 hour at a speed of 600rpm, and then transfer the powder to a spray dryer. Adjust the feed rate to 15ml / min, the inlet air temperature to 180~220℃, the atomization pressure to 0.2Mpa, and the outlet air temperature to 100℃. Then transfer the prepared product to a muffle furnace for sintering at 900℃ for 12h, and naturally cool to room temperature to obtain the positive electrode material, whose chemical formula is NaNi 0.3 Fe 0.3 Mn 0.4 O2.
[0083] (2) Weigh Na2CO3, MnO2, Ni(OH)2, Fe2O3, and Ti(C2O4)2 according to the stoichiometric ratio of 7:1.6:2.4:4:2 for the atoms of sodium, nickel, iron, manganese, and titanium, and slowly add them to 50 ml (4 mol / L) of oxalic acid solution while stirring. After the reaction is complete, transfer to a drying oven at 70°C and dry for 12 hours to obtain precursor 2.
[0084] (3) Take 10g NaNi 0.3 Fe 0.3 Mn 0.4 O2 material, 1g of precursor 2, mixed in a ball mill for 1 hour (rotation speed of 300rpm), calcined in a muffle furnace at 900℃ for 12h, and naturally cooled to room temperature to obtain material 1, the chemical formula of which is NaNi 0.3 Fe 0.3 Mn 0.4 O2@Na 0.7 (Ni 0.2 Fe 0.3 Mn 0.5 )0.8 Ti 0.2 O2.
[0085] (4) Take 10g of material 1 and 0.8g of Na3Zr2Si2PO 12 The material was mixed in a ball mill for 1 hour at a rotation speed of 300 rpm, then calcined in a muffle furnace at 500°C for 15 hours, and naturally cooled to room temperature to obtain a positive electrode material. 0.3 Fe 0.3 Mn 0.4 O2@Na 0.7 (Ni 0.2 Fe 0.3 Mn 0.5 ) 0.8 Ti 0.2 O2@Na3Zr2Si2PO 12 .
[0086] Comparative Example 5
[0087] A method for preparing a positive electrode material for a sodium ion battery, comprising:
[0088] (1) Weigh a certain amount of sodium carbonate, NiO, MnO2, Fe2O3, Ta2O5, and CeO2 as raw materials, where the molar ratio of sodium, nickel, manganese, iron, tantalum, and cerium is 10.3:2.4:2.4:3.2:1:1, and pour them into a ball mill. Add a certain amount of pure water to the ball mill to make the solid-liquid ratio 20:100 g / mL, mix in the ball mill for 1 hour at a speed of 600 rpm, and then transfer the powder to a spray dryer. Adjust the feed rate to 15 ml / min, the inlet air temperature to 180~220 °C, the atomization pressure to 0.2 MPa, and the outlet air temperature to 100 °C. Then transfer the prepared product to a muffle furnace for sintering at 900 °C for 12 hours, and naturally cool to room temperature to obtain a positive electrode material with a chemical formula of Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.8 (Ta 0.5 Ce 0.5 ) 0.2 O2.
[0089] (2) Weigh Na2CO3, Ni(OH)2, MnO2, and Fe2O3 according to the stoichiometric ratio of 7:2:3:5 for the atoms of sodium, nickel, iron, and manganese, and slowly add them to 50 ml (4 mol / L) of oxalic acid solution while stirring. After the reaction is complete, transfer to a drying oven at 70°C and dry for 12 hours to obtain precursor 2.
[0090] (3) Take 10g Na(Ni 0.3 Fe 0.3 Mn0.4 ) 0.8 (Ta 0.5 Ce 0.5 ) 0.2 O2 material, 1g of precursor 2, was mixed in a ball mill for 1 hour (rotation speed was 300rpm), then calcined in a muffle furnace at 900℃ for 12h, and naturally cooled to room temperature to obtain material 1, the chemical formula of which is Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.8 (Ta 0.5 Ce 0.5 ) 0.2 O2@Na 0.7 Ni 0.2 Fe 0.3 Mn 0.5 O2.
[0091] (4) Take 10g of material 1 and 0.8g of Na3Zr2Si2PO 12 The material was mixed in a ball mill for 1 hour at a rotation speed of 300 rpm, then calcined in a muffle furnace at 500°C for 15 hours, and naturally cooled to room temperature to obtain a positive electrode material. Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.8 (Ta 0.5 Ce 0.5 ) 0.2 O2@Na 0.7 Ni 0.2 Fe 0.3 Mn 0.5 O2@Na3Zr2Si2PO 12 .
[0092] Example 2
[0093] A method for preparing a positive electrode material for a sodium ion battery, comprising:
[0094] (1) Weigh a certain amount of sodium carbonate, NiO, MnO2, Fe2O3, Ta2O5, and CeO2 as raw materials, where the molar ratio of sodium, nickel, manganese, iron, tantalum, and cerium is 20.6:5.1:5.1:6.8:1.5:1.5, pour into a ball mill, add a certain amount of pure water to the ball mill to make the solid-liquid ratio 20:100 g / mL, mix in the ball mill for 1 hour at a speed of 600 rpm, and then transfer the powder to a spray dryer, adjust the feed rate to 15 ml / min, the inlet air temperature to 180-220 ° C, the atomization pressure to 0.2 MPa, and the outlet air temperature to 100 ° C. Transfer the prepared product to a muffle furnace for sintering at 850 ° C for 14 hours, and after natural cooling, obtain the core material Na(Ni 0.3 Fe0.3 Mn 0.4 ) 0.85 (Ta 0.5 Ce 0.5 ) 0.15 O2.
[0095] (2) Preparation of the sub-outer layer material: Weigh Na2CO3, Ni(OH)2, Fe2O3, MnO2, and Ti(C2O4)2 according to the stoichiometric ratio of 8:1.8:2.7:4.5:1 for the atoms of sodium, nickel, iron, manganese, and titanium, and slowly add them to 50 ml (4 mol / L) of oxalic acid solution while stirring. After the reaction is complete, transfer to a drying oven at 70°C and dry for 12 hours to obtain the sub-outer layer material precursor 2.
[0096] (3) Take 10g of the core material and 1g of the precursor 2, mix them in a ball mill for 1 hour (speed 300rpm), and then sinter them in a muffle furnace at 850℃ for 14h to obtain material 1. Then, the outer layer material is evenly distributed on the surface of the core material, and the chemical formula is: Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.85 (Ta 0.5 Ce 0.5 ) 0.15 O2@Na 0.8 (Ni 0.2 Fe 0.3 Mn 0.5 ) 0.9 Ti 0.1 O2.
[0097] (4) Take 10g of material 1 and 0.8g of Na3Zr2Si2PO 12 The material was mixed in a ball mill for 1 hour at a rotation speed of 300 rpm, then calcined in a muffle furnace at 600 ° C for 12 hours, and naturally cooled to room temperature to obtain the positive electrode material Na (Ni 0.3 Fe 0.3 Mn 0.4 ) 0.85 (Ta 0.5 Ce 0.5 ) 0.15 O2@Na 0.8 (Ni 0.2 Fe 0.3 Mn 0.5 ) 0.9 Ti 0.1 O2@Na3Zr2Si2PO 12 .
[0098] Example 3
[0099] A method for preparing a positive electrode material for a sodium ion battery, comprising:
[0100] (1) Weigh a certain amount of sodium carbonate, NiO, MnO2, Fe2O3, Ta2O5, and CeO2 as raw materials, where the molar ratio of sodium, nickel, manganese, iron, tantalum, and cerium is 10.3:2.7:2.7:3.6:0.5:0.5, pour into a ball mill, add a certain amount of pure water to the ball mill to make the solid-liquid ratio 20:100 g / mL, mix in the ball mill for 1 hour at a speed of 600 rpm, and then transfer the powder to a spray dryer, adjust the feed rate to 15 ml / min, the inlet air temperature to 180-220 °C, the atomization pressure to 0.2 MPa, and the outlet air temperature to 100 °C. Transfer the prepared product to a muffle furnace and sinter at 800 °C for 16 hours. After natural cooling, the core material Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.9 (Ta 0.5 Ce 0.5 ) 0.1 O2.
[0101] (2) Preparation of the sub-outer layer material: weigh Na2CO3, Ni(OH)2, Fe2O3, MnO2, and Ti(C2O4)2 according to the stoichiometric ratio of 5:1.7:2.55:4.25:1.5 for the atoms of sodium, nickel, iron, manganese, and titanium, and slowly add them to 50 ml (4 mol / L) of oxalic acid solution while stirring. After the reaction is complete, transfer to a drying oven at 70°C and dry for 12 hours to obtain the sub-outer layer material precursor 2.
[0102] (3) Take 10g of the core material and 1g of the precursor 2, mix them in a ball mill for 1 hour (speed 300rpm), and then sinter them in a muffle furnace at 800℃ for 16h to obtain material 1. Then, the outer layer material is evenly distributed on the surface of the core material, and the chemical formula is: Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.9 (Ta 0.5 Ce 0.5 ) 0.1 O2@Na 0.5 (Ni 0.2 Fe 0.3 Mn 0.5 ) 0.85 Ti 0.15 O2.
[0103] (4) Take 10g of material 1 and 0.8g of Na3Zr2Si2PO 12The material was mixed in a ball mill for 1 hour at a speed of 300 rpm, then calcined in a muffle furnace at 450°C for 16 hours, and naturally cooled to room temperature to obtain a positive electrode material. The SEM image of the obtained positive electrode material is shown in Figure 3 As shown; the XRD pattern of the obtained positive electrode material is shown Figure 4 As shown, from Figure 4 It can be seen that the positive electrode material includes characteristic peaks corresponding to the O3 phase and P2, and no other obvious impurity peaks can be seen. The chemical formula of the final positive electrode material is Na(Ni 0.3 Fe 0.3 Mn 0.4 ) 0.9 (Ta 0.5 Ce 0.5 ) 0.1 O2@Na 0.5 (Ni 0.2 Fe 0.3 Mn 0.5 ) 0.85 Ti 0.15 O2@Na3Zr2Si2PO 12 .
[0104] Example 4
[0105] The only difference between this embodiment and embodiment 1 is that in step (3), the amount of sodium-rich core material used is 10 g, and the amount of precursor 2 used is 2 g;
[0106] In step (4), 10 g of material 1 obtained in step (3) and 0.5 g of Na3Zr2Si2PO 12 The materials are used as raw materials to prepare positive electrode materials.
[0107] Example 5
[0108] The only difference between this embodiment and embodiment 1 is that in step (3), the amount of sodium-rich core material used is 10 g, and the amount of precursor 2 used is 1.5 g;
[0109] In step (4), 10 g of material 1 obtained in step (3) and 1 g of Na3Zr2Si2PO 12 The materials are used as raw materials to prepare positive electrode materials.
[0110] The positive electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were prepared into button-type batteries according to the following method.
[0111] In a clean room with humidity below 10%, weigh 0.4g of positive electrode material, 0.05g of polyvinylidene fluoride (PVDF) and 0.05g of acetylene black (C), grind the three materials in a mortar for 10 minutes, drop 2ml of N-methylpyrrolidone into them, dissolve them completely, and evenly apply them on the surface of Al foil with a scraper. Place the aluminum foil with slurry in a vacuum oven at 90℃ and dry for 10 hours, then cut it into a circular electrode with a diameter of 12mm on a cutting machine. The weight of the active material is about 3mg / cm 2 , sodium metal sheet was used as the anode of the battery, NaClO4 electrolyte (NC-019) and porous glass fiber (Whatman, GF / D) as the separator, and button cells were assembled in an argon-filled glove box.
[0112] The button cell was heated at 25°C with a voltage range of 2 to 4V at a rate of 1C (130mAg -1 ) rate for charge and discharge test, the cycle performance comparison is shown in the figure Figure 5 shown.
[0113] from Figure 5 It can be seen that the button-type batteries assembled with the positive electrode materials prepared in each embodiment have significantly improved discharge specific capacity and cycle performance compared with the button-type batteries assembled with the positive electrode materials prepared in each comparative example. By comparing the battery performance of Example 1 with Comparative Example 1 and Comparative Example 2, it can be found that the discharge specific capacity and cycle performance of the button-type batteries assembled with the positive electrode materials prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are ranked as follows: Example 1 is better than Comparative Example 2 and Comparative Example 3, and Comparative Example 2 and Comparative Example 3 are better than Comparative Example 1, indicating that whether the positive electrode material is modified by coating with a single material or by coating with multiple materials, the performance of the positive electrode material is improved compared with that of the positive electrode material that is not coated and modified; and the Ti-doped P2 phase positive electrode material is first coated on the surface of the Ta and Ce-doped O3 phase positive electrode material, and then coated with the ion conductor Na3Zr2Si2PO 12 The performance is better than that of the positive electrode material coated with only Ti-doped P2 phase positive electrode material and that coated with only Na3Zr2Si2PO 12 The results show that the Ti-doped P2 phase positive electrode material coating has a modification effect on the Ta and Ce-doped O3 phase positive electrode materials, which may be related to the fact that the sodium-deficient sub-outer layer can effectively reduce the Na + The diffusion barrier of Na3Zr2Si2PO4 can improve ion conduction and slow down the generation rate of surface residual alkali compared with O3 phase positive electrode materials. 12 The Ti-doped P2 phase cathode material coated with Ta and Ce-doped O3 phase cathode material has a further modification effect, which may be due to the Na3Zr2Si2PO 12It is an ion conductor material that can reduce the interfacial charge transfer impedance and enhance the ion diffusion kinetics. The material layer can stabilize the electrochemical interface, thereby improving the structural stability and electrochemical performance of the sodium ion battery.
[0114] By comparing Example 1 with Comparative Examples 4 and 5, it is found that when the base material or the intermediate layer material is not doped and modified, the electrochemical performance is also reduced, indicating that the modification of the positive electrode material can be achieved by doping the O3 phase core with Ta and Ce. It is speculated that the addition of Ta and Ce ions can expand the ion channel due to the large ion radius, stimulate and promote Fe 2+ / Fe 3+ 、Ni 3+ / Ni 4+ redox; the positive electrode material is also modified by doping the P2 phase intermediate layer with Ti. After analysis, this may be because the introduction of Ti ions can increase the redox potential, alleviate the slip of the transition metal layer during the charge and discharge process, and enhance the structural stability.
[0115] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A sodium ion battery positive electrode material, characterized in that: It includes an O3-type cathode material matrix and a P2-type sodium-ion cathode material layer and an ion conductor material layer sequentially arranged from inside to outside on the surface of the matrix; the O3-type cathode material matrix is a sodium metal oxide doped with Ta and Ce; the P2-type sodium-ion cathode material is a sodium metal oxide doped with Ti; the chemical formula of the sodium metal oxide doped with Ta and Ce is Na(Ni 0.3 Fe 0.3 Mn 0.4 ) y1 (Ta 0.5 Ce 0.5 ) z1 O2, where 0.8 < y1 ≤ 0.9 and 0.1 < z1 ≤ 0.2; the chemical formula of the sodium metal oxide doped with Ti is Na t (Ni 0.2 Fe 0.3 Mn 0.5 ) y2 Ti z2 O2, where 0.44 < t ≤ 0.8, 0.8 < y2 ≤ 0.9, and 0.1 < z2 ≤ 0.2; the ion conductor material is Na3Zr2Si2PO 12 ; the mass ratio of the matrix to the P2-type sodium-ion cathode material is 1:5 - 25 wt%; the mass ratio of the matrix to the ion conductor material is 1:5 - 10 wt%.
2. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, wherein: include: S1. preparing an O3 type positive electrode material matrix, wherein the O3 type positive electrode material matrix is a sodium metal oxide doped with Ta and Ce; S2, preparing a P2 type sodium ion cathode material precursor by an oxalic acid precursor method; S3, mixing the O3 type positive electrode material matrix with the P2 type sodium ion positive electrode material precursor, and calcining to obtain a material A in which the P2 type sodium ion positive electrode material is coated with the O3 type positive electrode material matrix; S4. Material A is mixed with an ion conductor material, and then calcined to obtain a sodium ion battery positive electrode material in which the ion conductor material coats the material A.
3. The method for preparing a positive electrode material for a sodium ion battery according to claim 2, characterized in that: In step S3, the calcination temperature is 700-900° C. and the calcination time is 12-24 hours.
4. The method for preparing a positive electrode material for a sodium ion battery according to claim 2, characterized in that: In step S4, the calcination temperature is 400-600° C. and the calcination time is 12-18 hours.
5. The method for preparing a positive electrode material for a sodium ion battery according to claim 2, characterized in that: Step S1 includes: using sodium source, nickel source, iron source, manganese source, tantalum source and cerium source as raw materials, wet mixing and ball milling, spray drying to obtain mixed powder, and high temperature sintering the mixed powder to obtain O3 type positive electrode material matrix Na (Ni 0.3 Fe 0.3 Mn 0.4 ) y1 (Ta 0.5 Ce 0.5 ) z1 O2, of which 0.8 <y1≤0.9,0.1<z1≤0.2。 6. The method for preparing a positive electrode material for a sodium ion battery according to claim 5, characterized in that: In step S1, the sodium source is one or more of sodium oxide, carbonate, hydroxide, and oxalate; the nickel source is one or more of nickel oxide, hydroxide, carbonate, oxalate, acetate, and nitrate; the iron source is one or more of iron oxide, hydroxide, carbonate, oxalate, acetate, and nitrate; the manganese source is one or more of manganese oxide, hydroxide, carbonate, oxalate, acetate, and nitrate; the tantalum source is one or more of tantalum oxide, hydroxide, carbonate, oxalate, acetate, and nitrate; the cerium source is one or more of cerium oxide, hydroxide, carbonate, oxalate, acetate, and nitrate; In step S1, the temperature of the high temperature sintering is 700-900° C., and the time of the high temperature sintering is 12-18 hours.
7. The method for preparing a positive electrode material for a sodium ion battery according to claim 2, characterized in that: Step S2 includes: adding a sodium source, an iron source, a nickel source, a manganese source and a titanium source into an oxalic acid solution, reacting the solution, and drying the solution to obtain an oxalate precursor.
8. The method for preparing a positive electrode material for a sodium ion battery according to claim 7, characterized in that: In step S2, the sodium source is one or more of sodium oxide, carbonate, and oxalate; the nickel source is one or more of nickel oxide, hydroxide, carbonate, oxalate, and acetate; the manganese source is one or more of manganese oxide, hydroxide, carbonate, oxalate, and acetate; the iron source is one or more of iron oxide, hydroxide, carbonate, oxalate, and acetate; and the titanium source is titanium oxalate.
9. A sodium ion battery, characterized in that: It includes the sodium ion battery positive electrode material as claimed in claim 1 or the sodium ion battery positive electrode material prepared by the preparation method as claimed in any one of claims 2 to 8.
